The Impact of Public Relations on Crisis Management: A Case Analysis of Aramco’s Oil Spill Incident (International Journal of Financial, Administrative and Economic Sciences, 2025)
This paper seeks to examine the role of public relations in crisis management, drawing on a case study of Aramco during the oil spill. This study aims to examine the role of public relations in improving crisis response and maintaining reputation within the oil sector, taking into account the critical nature of crisis management and its significant impacts on the environment and the economy. The research employed a quantitative methodology, distributing a questionnaire to a sample of 140 Aramco employees and relevant stakeholders to collect baseline data to assess the impact of public relations on crisis management. The questionnaire covered several dimensions related to the various functions of public relations within the organization, ranging from enhancing risk management to increasing reputation and strengthening internal and external relations. After collecting responses, the data was subjected to statistical analysis to provide accurate and objective results. The study results demonstrate that public relations significantly enhances Aramco's crisis response by guiding communication tactics and managing disseminated information, thereby reducing the spread of rumors and helping contain the crisis. The results indicated that public relations enhances the company's reputation by increasing openness and trust while disseminating positive messages regarding Aramco's crisis management procedures. The study emphasized the importance of public relations in strengthening relationships between the organization and its stakeholders, thereby enhancing trust and mitigating tensions during crises. The study concluded that public relations is essential in Aramco's crisis management, enhancing response strategies, improving reputation, and strengthening relationships, thereby mitigating the severity of the crisis and ensuring continued effective institutional performance.
Keywords: Public Relations; Crisis Management; Oil Spill